Meta Analysis: Correlation between Diabetes Mellitus and Surgical Wound Infection - Fahrezi, Chattrin; Murti, Bhisma; Tamtomo, Didik (Indonesian Journal of Medicine, 2022)
Background: Surgical wound infections complicate 10-20% of operations with a considerable burden of increasing morbidity, mortality, and health care costs. One third of postoperative deaths are associated with surgical wound infections. The risk of surgical site infection is associated with the presence of risk factors for diabetes mellitus. This causes patients undergoing surgery with diabetes mellitus to have a higher risk of developing surgical site infections. This study aims to examine the effect of diabetes mellitus on the incidence of surgical wound infection.Subjects and Method: This research was conducted using a systematic review design and meta-analysis using PRISMA flow diagrams. The article search was conducted by selecting articles published between the years 2000-2022 which were obtained from several databases of PubMed, Google Scholar, Science Direct, and Springer Link. The keywords used to search for articles were “Diabetes Mellitus”, “Surgical Site Infection”, “cohort”, “Diabetes Mellitus” AND “Surgical Site Infection”, “Diabetes Mellitus” AND “Surgical Site Infection” AND “adjusted odd ratio”. The analysis was carried out using RevMan 5.3 software.Results: Meta-analysis of 9 articles of diabetes mellitus (aOR= 2.54; 95% CI= 1.93 to 3.34; p<0.001) affected the incidence of surgical wound infection.Conclusion: Diabetes mellitus increases the incidence of surgical wound infections.Keywords: diabetes mellitus, surgical wound infectionCorrespondence: Chattrin Fahrezi. Masters Program in Public Health, Universitas Sebelas Maret, Jl.Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: chattrinfahrezi311@gmail.com. Mobile: 08812532292.Indonesian Journal of Medicine (2022), 07(02): 122-130https://doi.org/10.26911/theijmed.2022.07.02.01